Development of a READING (Reading, Exploring, Analyzing, Discussing, and Narrating) Model Grounded in Multiculturalism to Strengthen Cultural Literacy in Children's Literature Learning - Opik, Opik; Sunendar, Dadang; Damayanti, Vismaia S.; Maftuh, Bunyamin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop the READING Model (Reading, Exploring, Analyzing, Discussing, and Narrating) based on multiculturalism to strengthen cultural literacy in children's literature learning. The model is grounded in transactional reader-text theory, sociocultural approaches, and cultural competence. This study used an educational design research (EDR) approach, involving problem identification, prototype development, trial and refinement, and implementation and reflection. Data were collected through model validation assessment sheets, implementation observations, reflective interviews, documentation, and testing, and analyzed using thematic analysis and statistical tests. The model was tested on 137 fifth-grade students from six elementary schools in Tasikmalaya City. The results show that the model is highly valid (average score of 3.55 from experts and 3.57 from practitioners), practical (implementation rates of 94.29%, 97.14%, and 100% in three schools), and effective in improving students' learning outcomes in cognitive, affective, and psychomotor domains.